2009
DOI: 10.4103/0377-4929.56157
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the external auditory canal: Report of two cases

Abstract: Adenoid cystic carcinoma occurring in the external auditory canal is very rare. Two cases are being reported. One was diagnosed on cytology based on which surgery was planned. In the second case, fine needle aspiration procedure had to be abandoned due to severe pain and a biopsy was required for its diagnosis. Morphologically, it resembles its more common salivary gland counterpart. Though severe pain during needling may be a limiting factor, adenoid cystic carcinoma of external auditory canal can be confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A review of all three cases of this type of tumor, including the two previously reported cases as well as the present one, revealed that the cytological features include: (i) the presence of spherical globules surrounded by cohesive, uniform round tumor cells and (ii) tumor cells with scant cytoplasm, hyperchromatic nuclei, and visible to inconspicuous nucleoli. 4,5 These features are identical to those of ACC of the salivary gland. 6 Nagel et al reported on the cytological differential diagnosis of ACC of the salivary gland, and they concluded that pleomorphic adenoma (PA), basal cell adenoma/adenocarcinoma, and skin appendage tumors, such as cylindroma and spiradenoma should be included in the differential diagnostic consideration.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…A review of all three cases of this type of tumor, including the two previously reported cases as well as the present one, revealed that the cytological features include: (i) the presence of spherical globules surrounded by cohesive, uniform round tumor cells and (ii) tumor cells with scant cytoplasm, hyperchromatic nuclei, and visible to inconspicuous nucleoli. 4,5 These features are identical to those of ACC of the salivary gland. 6 Nagel et al reported on the cytological differential diagnosis of ACC of the salivary gland, and they concluded that pleomorphic adenoma (PA), basal cell adenoma/adenocarcinoma, and skin appendage tumors, such as cylindroma and spiradenoma should be included in the differential diagnostic consideration.…”
mentioning
confidence: 58%
“…Thus far, only two cytolǒgical reports on ACC of the EAC have been reported. 4,5 Herein, we describe the cytological analysis of the third case of this tumor and discuss the usefulness of fine needle aspiration (FNA) in diagnosis of glandular tumor of the EAC.…”
mentioning
confidence: 99%
“…To the best of our knowledge, only a few reports have included >3 patients with ACC of the EAC (4,(15)(16)(17), with other studies being reports of single cases (11,(18)(19)(20)(21)(22)(23)(24)(25)(26). Due to the rarity of the disease, the natural course and treatment of ACC of the EAC remain poorly understood, and there are no guidelines for the diagnosis and management of this malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoid cystic carcinoma of the external auditory canal can be confidently diagnosed on the basis of cytology on which surgical management could be planned . (5) Adenoid cystic carcinoma may locally invade soft tissue and bone , extend into parotid gland and temporomandibular joint , invade by perineural and perivascular extension and metastasize too regional lymph nodes ,lungs…”
Section: Discussionmentioning
confidence: 99%